Heat transfer enhancement in three-start spirally corrugated tube: experimental and numerical study - Kareem, Zaid Sattar (Elsevier, 2015)
Recently, the employing of corrugation for the enhancement of heat transfer has become interesting because it has the combined merits of extended surfaces, turbulators and roughness. Studies employing the use of both experimental and numerical techniques for the determination of thermal performance of spirally corrugated tubes for the flow of water at low Reynolds number are limited. Therefore, an experimental and numerical study for the flow of water at low Reynolds number in a spirally corrugated tubes was performed to determine the thermal performance of a new style of corrugation profile. The overall thermal performance was calculated for corrugated tubes, the numerical data of both Nusselt number and friction factor have been compared with the experimental data for standard smooth and corrugated tube. The results showed heat transfer enhancement range of 2.4-3.7 times of smooth tube with appreciable increase in the friction factor of 1.7-2.4 times of smooth tube. It observed and concluded that for long term and wide usage range, the tube of severity index value of 36.364×10-3 has the best thermal performance of 1.8-3.4 at Reynolds number of 100-1300. This indicated that this geometry with a creative spiral corrugation profile can improve the heat transfer significantly with reasonable increase in friction factor